Enhanced quantum efficiency in polymer light-emitting diode with polystryrene nanolayer - Park, JH; Park, OO; Yu, JW; Kim, JK; Kim, YC (TAYLOR & FRANCIS LTD, 2004)
We report the effect of polystyrene nanolayer on electron injection in the polymer light-emitting diodes (PLEDs) in which hole is major charge carrier. Especially, when a similar to10 nm-thick polystyrene layer was employed, the device gave two orders of magnitude higher external quantum efficiency than that of the one without an insulating nanolayer This enhancement may result from the dramatic lowering of the effective barrier height for electron injection to the emitting layer.